Sediment accumulation rate predicts the temporal resolution of marine fossil assemblages - Michał Kowalewski; Adam Tomašových; Rafał Nawrot; Daniele Scarponi; Martin Zuschin; Paolo G. Albano; Quan Hua; Darrell S. Kaufman; Susan M. Kidwell; Matias Ritter; Marcello G. Simões; Luis Torres; et al. (Proceedings of the National Academy of Sciences, 2026)
Time averaging (TA), the mixing of noncontemporaneous organisms in fossil assemblages, governs the resolution of paleontological data and determines which biological and environmental processes are recorded in the geological record. To assess variation in TA and its dependence on external drivers, we used amino acid and radiocarbon methods to individually date 7,593 specimens across 384 samples from late Quaternary marine assemblages of calcifying organisms. Bivalve mollusks dominated the data, but 65 samples represented other taxa. Estimates of TA, measured by dispersion of specimen ages within samples, ranged from decades to millennia and scaled proportionally ( r 2 = 0.77) with sediment accumulation time (SAT), an inverse of sediment accumulation rate (SAR) that accounts for the stratigraphic span of samples. In agreement with numerical modeling, the observed TA estimates were an order-of-magnitude higher than SAT and modulated by SAT-dependent effects of vertical mixing and skeletal disintegration. When SAT is short, effective disintegration rates are too slow to suppress the amplifying role of mixing but increase in importance when SAT is long. The strong dependency of TA on SAT points to the overriding role of SAR in controlling the temporal resolution of fossil assemblages, notwithstanding other interacting drivers known to influence TA. These results demonstrate a long-suspected paleontological rule: The temporal resolution of fossil assemblages scales predictably with SAR. This straightforward relationship provides a quantitative guideline for determining the temporal adequacy of sedimentary records as archives of Earth system processes.